Relationship Between Albumin Levels and Leukocyte Counts in The Incident of Neonatal Sepsis - Sulaiman, Shofan Ilham; Haryanto, Edy; Endarini, Lully Hanni (Poltekkes Kemenkes Mataram, 2023)
Background: Sepsis can affect all age, but is most common in young infants and neonates. Young infants and neonates are more susceptible to infection because their immune systems are immature, unable to localize infections, and lack the IgM needed to protect the body against bacterial infections. When experiencing neonatal sepsis, there is often an increase in leukocytes in response to infection and inflammation, where inflammation can also cause a decrease in albumin in the blood. Objective: This study aims to analyze the relationship between albumin levels and leukocyte counts in the incidence of neonatal sepsis. Methods: The research method used analytic correlation with a cross sectional approach. A sample of 31 patients with neonatal sepsis who were treated at Waluyo Jati hospital, Probolinggo Regency in December 2022 - April 2023 were sampled using saturation sampling method. Results: The results of the study on neonatal sepsis based on laboratory examinations mostly occurred in conditions of leukocytosis (45.2%) and hypoalbuminemia (77.4%), while the results of the study based on Pearson correlation test analysis obtained a significant value (p) of 0.737 (α=0.05). Conclusion: there is no relationship between albumin levels and leukocyte counts in neonatal sepsis.